Public Relations Management in an Effort to Improve School Branding Through the “Program Gerbang” - Maswanda Fazriyati; Marno Marno; Akhmad Nurul Kawakip (Journal of Educational Management Research, 2024)
Public relations management in schools must work actively in efforts to improve school branding. Moreover, the current conditions of the development of the era of globalization and increasingly tight school competition. Schools must also innovate in creating their school's characteristics. Madrasas has a unique school program, namely the Gerbang program (enthusiasm for foreign languages). This program not only improves foreign language skills but also contributes to forming the school's identity or brand. Therefore, it is necessary to improve public relations through this Gerbang program to improve school branding. The purpose of the study was to determine, the public relations management process in an effort to improve school branding through the Gerbang program. Public relations model of madrasas in efforts to improve school branding in the implementation of the Gerbang program. Implications of the Gerbang program in efforts to improve school branding. The type of research in this study is a case study with a qualitative approach. The impact is increasing the attractiveness of prospective students, increasing achievement, increasing the reputation of the sekolah, increasing student confidence, increasing social media followers.